An Unusual Case of Ectopic ACTH Syndrome - Willhauck, M. J.; Pöpperl, G.; Rachinger, W.; Giese, A.; Auernhammer, C. J; Spitzweg, C. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Ectopic ACTH-syndrome is a rare cause of Cushing’s disease. Despite extensive diagnostic procedures the source of ACTH secretion often remains occult.This case describes a 45-year old woman with an ectopic Cushing’s syndrome. Extensive imaging procedures including CT scan of chest and abdomen, octreotide scan and MRI of the chest and pituitary did not reveal the source of ACTH secretion.In consideration of an occult source of ACTH secretion we started a therapeutic trial with cabergoline (0.5 mg/d), a dopamine receptor agonist, which has been shown to be effective in ectopic Cushing’s syndrome. 2 months after cabergoline treatment had been initiated, ACTH and cortisol levels normalized in association with significant improvement of the clinical symptoms.During follow-up a [68Ga-DOTA-dPhe1, Tyr3]-octreotate ([68Ga-DOTA]-TATE) PET-CT was performed revealing a somatostatin receptor positive lesion in the right sphenoidal sinus suggesting the source of ACTH secretion. The patient was cured by transnasal resection of the polypoid lesion, which was immunohistochemically characterized as an ACTH-positive neuroendocrine tumor.This case report demonstrates the management of ectopic ACTH-syndrome by molecularly targeted therapy with dopamine receptor agonists as well as improved detection of the ectopic ACTH source by novel imaging modalities, such as [68Ga-DOTA]-TATE PET specifically targeting somatostatin receptor subtype-2 with high affinity.
Keywords: pituitary adenoma; glucocorticoids; cabergoline; DOTA-TATE-PET